517PHigh BRCA1 expression is independently correlated with decreased overall survival in lung adenocarcinoma: Evidence from meta and bioinformatics analyses. (24th November 2019) - Guo, F; Zhang, Y; Li, Z; Tu, L; He, J; Huang, Y; Liu, K; Luo, F
Abstract: Background: The prognostic predictive value of breast cancer susceptibility gene 1 (BRCA1) for non-small-cell lung cancer (NSCLC) remains controversial. This study aimed to determine the prognostic effect of BRCA1 on NSCLC survival using meta-bioinformatic analysis. Methods: Candidate articles were identified from PubMed, Embase, Cochrane Library, and Web of Science databases. Effect measures generated were the pooled hazard ratio (HR) and 95% confidence interval (CI). Cox regression model was performed in an independent dataset from TCGA to validate the accuracy of our meta-analysis. Results: A total of 2462 patients from 15 studies of acceptable quality were included. No significant differences in overall survival (OS)/cancer-specific survival (CSS) (HR = 1.38, 95% CI: 0.95-2.00, P = 0.094) or progression-free survival (PFS)/disease-free survival (DFS)/relapse-free survival (RFS) (HR = 1.28, 95% CI: 0.82-2.00, P = 0.284) were observed between patients with high- and low-expression of BRCA1. However, patients with lung adenocarcinoma (LUAD) and increased BRCA1 expression had markedly poorer OS/CSS (HR = 1.78, 95% CI: 1.05-3.03, P = 0.032) than those with reduced BRCA1. Bioinformatics analysis also indicated that BRCA1 overexpression was independently correlated with decreased OS in LUAD. Moreover, patients with high BRCA1 were more likely to suffer from lymph node metastasis than those with low BRCA1. Conclusions: Elevated BRCA1 expression may be a novel biomarker of poor OS for patients with LUAD. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.